Upregulation of Antioxidative Gene Expression by Lasia spinosa Organic Extract Improves the Predisposing Biomarkers and Tissue Architectures in Streptozotocin-Induced Diabetic Models of Long Evans Rats - Farjana Sharmen; Md. Atiar Rahman; A. M. Abu Ahmed; Tanvir Ahmed Siddique; Md. Khalid Juhani Rafi; Jitbanjong Tangpong (MDPI AG, 2022)
Plants are an entity essential to the function of the biosphere as well as human health. In the context of human health, this research investigated the effect of Lasia spinosa (Lour) leaf methanolic extracts (LSML) on antioxidative enzymes and gene expression as well as biochemical and histological markers in a streptozotocin (STZ)-induced diabetes model. Fructose-fed streptozotocin (STZ)-induced diabetic animals were subjected to a four-week intervention followed by the assessment of the animal's blood and tissues for enzymatic, biochemical, histological, and genetic changes. LSML-treated groups were shown to decrease plasma glucose levels and improve body and organ weights compared to the untreated group in a dose-dependent manner. At the doses of 125 and 250 mg/kg b.w., LSML were able to normalize serum, hepatic, and renal biochemical parameters and restore the pancreas, kidney, liver, and spleen tissue architectures to their native state. A considerable increase (p < 0.01) of liver antioxidant enzymes CAT, SOD, GSH, and a decrease of MDA level in LSML-treated groups were found at higher doses. The improved mRNA expression level of antioxidant genes CAT, SOD2, PON1, and PFK1 was also found at the doses of 125 mg/kg and 250 mg/kg BW when compared to untreated control groups. The results demonstrate that LSML impacts the upregulation of antioxidative gene expressions, thus improving the diabetic complications in animal models which need to be affirmed by compound-based antioxidative actions for therapeutic development.